The Impact of Investment Opportunities, Financial Performance, Internal Mechanisms on Earnings Quality - Aryffin , Elvina Stephanie; Sutrisno, Paulina (Media Bisnis, 2024)
This research aims to provide empirical evidence regarding the influence of investment opportunities, financial performance as manifested by return on assets (ROA) ratio, company size, liquidity ratio as manifested by the current ratio, growth opportunities, and internal mechanisms such as audit committee, institutional ownership on earnings quality and the relationship between these factors and earnings quality. The study utilizes a sample of non-cyclical and cyclical companies during the research period of 2020-2022. Hypothesis testing in this study employs multiple linear regression. The results of the research indicate that the factor influencing earnings quality is financial performance. Meanwhile, investment opportunities, company size, liquidity, audit committee, growth opportunities, and institutional ownership do not influence earnings quality.